Barriers and Facilitators of Stroke Recovery: Perspectives From African Americans With Stroke, Caregivers and Healthcare Professionals - Magwood, Gayenell S. (J Stroke Cerebrovasc Dis, 2019)
INTRODUCTION AND GOAL: Stroke is a serious health condition that disproportionally affects African-Americans relative to non-Hispanic whites. In the absence of clearly defined reasons for racial disparities in stroke recovery and subsequent stroke outcomes, a critical first step in mitigating poor stroke outcomes is to explore potential barriers and facilitators of poststroke recovery in African-American adults with stroke. The purpose of this study was to qualitatively explore poststroke recovery across the care continuum from the perspective of African-American adults with stroke, caregivers of African-American adults with stroke, and health care professionals with expertise in stroke care. MATERIALS AND METHODS: This qualitative descriptive study included in-depth key informant interviews with health care providers (n = 10) and focus groups with persons with stroke (n = 20 persons) and their family members or caregivers (n = 19 persons). Data were analyzed using thematic analysis according to the Social Ecological Model, using both inductive and deductive approaches. FINDINGS: Persons with stroke and their caregivers identified social support, resources, and knowledge as the most salient factors associated with stroke recovery. Perceived barriers to recovery included: (1) physical and cognitive deficits, mood; (2) medication issues; (3) lack of support and resources; (4) stigma, culture, and faith. Health care providers identified knowledge/information, care coordination, and resources in the community as key to facilitating stroke recovery outcomes. CONCLUSIONS: Key findings from this study can be incorporated into interventions designed to improve poststroke recovery outcomes and potentially reduce the current racial-ethnic disparity gap.